Association of tumour mutational burden with outcomes in patients with advanced solid tumours treated with pembrolizumab: prospective biomarker analysis of the multicohort, open-label, phase 2 KEYNOTE-158 study. Issue 10 (October 2020) - Marabelle, Aurélien; Fakih, Marwan; Lopez, Juanita; Shah, Manisha; Shapira-Frommer, Ronnie; Nakagawa, Kazuhiko; Chung, Hyun Cheol; Kindler, Hedy L; Lopez-Martin, Jose A; Miller, Wilson H; Italiano, Antoine; Kao, Steven; et al.
Summary: Background: Tumour mutational burden (TMB) has been retrospectively correlated with response to immune checkpoint blockade. We prospectively explored the association of high tissue TMB (tTMB-high) with outcomes in ten tumour-type-specific cohorts from the phase 2 KEYNOTE-158 study, which assessed the anti-PD-1 monoclonal antibody pembrolizumab in patients with selected, previously treated, advanced solid tumours. Methods: In the multi-cohort, open-label, non-randomised, phase 2 KEYNOTE-158 study, patients were enrolled from 81 academic facilities and community-based institutions across 21 countries in Africa, the Americas, Asia, and Europe. Eligible patients were aged 18 years or older, had a histologically or cytologically confirmed advanced (ie, unresectable or metastatic, or both) incurable solid tumour (eligible tumour types were anal, biliary, cervical, endometrial, mesothelioma, neuroendocrine, salivary, small-cell lung, thyroid, and vulvar), progression on or intolerance to one or more lines of standard therapy, had measurable disease per Response Evaluation Criteria in Solid Tumors (RECIST; version 1.1) assessed by independent central radiological review, Eastern Cooperative Oncology Group performance status of 0 or 1, life expectancy of at least 3 months, adequate organ function, and a tumour sample for biomarker analysis. Participants were given pembrolizumab 200 mg intravenously every 3 weeks for up to 35 cycles. Tissue TMB (tTMB) was assessed in formalin-fixed paraffin-embedded tumour samples using the FoundationOne CDx assay (Foundation Medicine, Cambridge, MA, USA). The prespecified definition of tTMB-high status was at least 10 mutations per megabase. The primary endpoint was the proportion of patients with an objective response (complete or partial response) as per Response Evaluation Criteria in Solid Tumours (version 1.1) by independent central review. This prespecified analysis assessed the association between antitumour activity and tTMB in treated patients with evaluable tTMB data. Efficacy was assessed in all participants who received at least one dose of pembrolizumab, had evaluable tTMB data, and were enrolled at least 26 weeks before data cutoff (June 27, 2019), and safety was assessed in all participants who received at least one dose of pembrolizumab and had tTMB-high status. KEYNOTE-158 is registered at ClinicalTrials.gov, NCT02628067, and is ongoing. Findings: Between Jan 15, 2016, and June 25, 2019, 1073 patients were enrolled. 1066 participants were treated as of data cutoff (June 27, 2019), of whom 805 (76%) were evaluable for TMB, and 105 (13%) of 805 had tTMB-high status and were assessed for safety. 1050 (98%) of 1066 patients enrolled by at least 26 weeks before data cutoff, of whom 790 (75%) were evaluable for TMB and included in efficacy analyses. 102 (13%) of these 790 patients had tTMB-high status (≥10 mutations per megabase), and 688 (87%) patients had non-tTMB-high status (<10 mutations per megabase). Median study follow-up was 37·1 months (IQR 35·0–38·3). Objective responses were observed in 30 (29%; 95% CI 21–39) of 102 patients in the tTMB-high group and 43 (6%; 5–8) of 688 in the non-tTMB-high group. 11 (10%) of 105 patients had treatment-related serious adverse events. 16 (15%) participants had a grade 3–5 treatment-related adverse event, of which colitis was the only such adverse event that occurred in more than one patient (n=2). One patient had fatal pneumonia that was assessed by the investigator to be treatment related. Interpretation: tTMB-high status identifies a subgroup of patients who could have a robust tumour response to pembrolizumab monotherapy. tTMB could be a novel and useful predictive biomarker for response to pembrolizumab monotherapy in patients with previously treated recurrent or metastatic advanced solid tumours. Funding: Merck Sharp & Dohme Corp, a subsidiary of Merck & Co, Inc.